Red Blood Cell Salvage During Obstetric Hemorrhage. Issue 1 (March 2016) - Milne, M.E.; Yazer, M.H.; Waters, J.H.
Abstract : ( Obstet Gynecol. 2015;125(4):919–923) The use of intraoperative blood salvage during postpartum hemorrhage is increasing. Reinfusion of the patient's own blood is now recommended by many national organizations as a tool during management of obstetric hemorrhage. This study analyzes 8 years of use in obstetric patients who lost enough blood during obstetric hemorrhage to receive a reinfusion.